Transcatether Aortic Valve Implantation to Treat Degenerated Surgical Bioprosthesis: Focus on the Specific Procedural Challenges - Aurigemma, Cristina; Burzotta, Francesco; Vergallo, Rocco; Farina, Piero; Romagnoli, Enrico; Cangemi, Stefano; Bianchini, Francesco; Nesta, Marialisa; Bruno, Piergiorgio; D'Amario, Domenico; Leone, Antonio Maria; Trani, Carlo (Frontiers in Cardiovascular Medicine, 2022)
Currently transcatheter aortic valve implantation within failed surgically inserted bioprosthetic valves (VIV-TAVI) has become an established procedure for patients deemed at high risk for repeat aortic valve intervention. Although less invasive than surgical reoperation, challenges of VIV- TAVI treatment include higher rates of prosthesis-patient mismatch and coronary obstruction. Thus, optimal preprocedural planning is of the utmost importance to minimize the risk of these complications. In this review, we describe the key points of a VIV TAVI procedure to optimize outcomes and minimize the risk of operative complications.